Efficacy of ceftazidime-avibactam for the treatment of central nervous system infection caused by carbapenem-resistant Klebsiella pneumoniae after neurosurgery - Cong, Wenkai; Qi, Guanghong; Wang, Shengjie; Bai, Zhenwei; Wang, Lin; Chen, Hongwei (Frontiers in Neurology, 2025)
BackgroundCarbapenem-resistant Klebsiella pneumoniae (CRKP) infections of the central nervous system (CNS) are associated with high mortality rates. These infections are particularly challenging to treat due to both bacterial resistance and the protective blood–brain barrier. This study aims to evaluate treatment outcomes for CRKP-induced CNS infections and provide insights into effective therapeutic strategies for similar cases.MethodsA retrospective analysis was conducted on patients with CRKP-positive cerebrospinal fluid (CSF) samples admitted to the CSF Neurosurgery Department of the Aviation General Hospital between August 2019 and November 2021. Data collected included patient demographics, medical history, laboratory results, etiological findings, and antibiotic treatments. Nine patients with CRKP-induced CNS infections who were treated with Ceftazidime-avibactam (CAZ-AVI) were included in the analysis. The study assessed clinical features, treatment courses, and patient outcomes.ResultsOf the nine patients, 88.9% (8/9) achieved both clinical and etiological cure. One patient experienced relapse 20 days after initial CSF culture negativity, with the family opting for discontinuation of further treatment. Following infection resolution, patients exhibited varying degrees of neurological improvement, including one case of complete recovery from a comatose state (GCS 6 to GCS 15). Treatment-related adverse effects included transient liver dysfunction in one patient and diarrhea in three, which resolved with symptomatic management. CSF drainage tubes were removed in three patients following treatment, while five required shunt surgery due to hydrocephalus. No relapses were reported in treated patients during a follow-up period of 3–12 months.ConclusionIntravenous CAZ-AVI combined with intracerebroventricular or intrathecal polymyxin B or amikacin demonstrated promising efficacy as a treatment regimen for CRKP-induced CNS infections.